Study of drying methods and chemical treatments on quality aspects of chilli cv.LCA 334 - P Venkata Reddy, C Ravi Shankar, K Uma Jyothi, S Surya Kumari, (Journal of Spices and Aromatic Crops, 2008)
The experiment to using chilli Cv. LCA 334 was conducted at Regional Agricultural ResearchStation. Lam, Guntur during the year 2003-2004. The results revealed significant differencesamong different drying methods and chemical treatments and their interactions on qualityconstituents of chilli viz; oleoresin, capsanthin and capsaicin. Among the drying methods ,Tobacco barn drying gave the highest oleoresin content of 10.5% and was found superior tothe other methods of drying viz; ground, tarpaulin and mechanical drying. However, thechemicals viz; BHA (Butylated Hydroxy Anisole), potassium carbonate and dipsol used fordrying did not exert significant influence on oleoresin content. Among the interactions,chilli treated with dipsol and dried in tobacco barn recorded the highest oleoresin content of10.7% followed by chilli treated with BHA and dried in tobacco barn (10.5%). With regard tocapsanthin content, the chilli dried in mechanical drier recorded the highest value (14503EOA colour value) followed by tobacco barn drying (13893 EOA colour value) and werefound superior to chilli dried on ground / tarpaulin. Among the chemical treatments, chillitreated with dipsol recorded the highest capsanthin content (13923 EOA colour value) andfound significantly superior to all the other treatments tried.. With regard to the capsaicincontent, chilli dried in tobacco barn recorded the highest capsaicin content (0.502%), closelyfollowed by chilli dried on ground (0.498%) and were found on par with each other andsignificantly superior to tarpaulin and mechanical drying.. Among the chemicals, BHAsignificantly increased the capsaicin content (0.508%) and found superior to check (0.468%)and also the other chemicals tried. Among the interactions, chilli treated with BHA anddried in tobacco barn recorded the highest capsaicin content (0.576%) and found significantlysuperior to all other interactions.